Reverse gyrase; ATP-dependent type I topoisomerase from Sulfolobus - Nakasu, Syo (1985)
Reverse gyrase, a topoisomerase which introduces positive superhelical turns into DNA, has been purified from Sulfolobus to near homogeneity. It is a single polypeptide with a mol. wt. of 120 000 as determined by denaturing gel electrophoresis. Contrary to a previous report, it is a type I topoisomerase as judged by the linking-number change of closed circular DNA topoisomer. Unlike other known type I topoisomerases, ATP or dATP is required for introducing positive superhelical turns. In order to relax negatively supercoiled DNA, other nucleotide triphosphates (XTP) are also effective with low efficiency. In the absence of either XTP or divalent cations, the enzyme introduces nicks into closed circular DNA when the reaction is stopped by SDS. This suggests that reverse gyrase cuts one of the two strands of DNA in the course of its enzymatic reaction.